The Effect of Booklets as Educational Media on Adolescent Women Knowledge About Breast Self Examination at High School Students - Ayu Mei Nursasi; Kris Linggardini (UM Purwokerto Press, 2022)
Background: Breast cancer is a malignancy that previously originated in glandular cells. Glandular ducts and the supporting tissues of the breast. Cancer can begin to grow in the breast glands or in the breast ducst, fat tissue or tissue that binds to the breast. Early detection of breast cancer can be done with breast self examination, Clinical examination and mammogram examination. From the results of a preliminary study condected on December 23, 2021 at State 1 Senior High School Randudongkal in Central Java. It was found that 7 students had been interviewed and the result were 4 out of 7 students at State 1 Senior Hight School Randudongkal for knowledge about breast self examination was still low or lacking and based on information obtained from the school that has never received counseling about breast self examinations. Objective: This research to identify the effect of booklets as educational media on adolescent womens knowledge about breast self examination in class x and xi at state 1 senior hight school randudongkal. Method: This research was quantitative research using Quasi Experimental research design and One Group Pre-Test Pos-Test Design. The sample in this study was 82 students of class X and XI of State 1 Senior Hight School Radudongkal for wichh were taken using the Slovin formula. The sampling technique used in this study was simple random samping. Results: The results showed that the Wilcoxon test on the respondent’s knowledge of breast cancer and the breast self examination showed that the calculated Z value was -7.830 and a significant value was 0.000. this shows that the significant value of 0.000 is less concluded that there is an effect on giving bookts as a medium for students knowledge of breast self examination. Conclusion: There is an affect of booklets as educational media on adolescent womens knowledge about breast self examination in grade x and xi at state 1 senior hight school randudongkal.